Synthesis of Stimuli-responsive Hydrogels from Glycerol - Salehpour, Somaieh (Université d'Ottawa / University of Ottawa, 2012)
Due to an increased environmental awareness and thus, concerns over the use of fossil-based monomer for polymer production, there is an ongoing effort to find alternatives to non-renewable traditional monomers. This has ushered in the rapid growth in the development of bio-based materials such as green monomers and biodegradable polymers from vegetable and animal resources. Glycerol, as a renewable bio-based monomer, is an interesting candidate for sustainable polymer production. Glycerol is a renewable material that is a by-product of the transesterification of vegetable oils to biodiesel. Utilization of the excess glycerol derived from the growing biodiesel industry is important to oleochemical industries. The main objective of this thesis was to produce high molecular weight polyglycerol from glycerol and synthesize stimuli-responsive polyglycerol hydrogels. The work began with an investigation of the step-growth polymerization of glycerol to relatively high molecular weight polyglycerol using several catalysts. The catalytic reaction mechanisms were compared and the polymer products were fully analyzed. High molecular weight partially branched polyglycerol with multimodal molecular weight distributions was obtained. The polymerization of glycerol proceeded fastest with sulphuric acid as catalyst as indicated by the highest observed conversion of monomer along with the highest molecular weights. Theoretical models were used to predict the gel point and to calculate monomer functionality. High molecular weight polyglycerol was used to synthesize novel stimuli-responsive hydrogels. Real-time monitoring of step-growth polymerization of glycerol was investigated using in-line and off-line Attenuated Total Reflectance/Fourier Transform infrared (ATR-FTIR) technique.
Keywords: monomer; polyglycerol; glycerol; Hydrogel; stimuli-responsive polyglycerol hydrogels